2013
DOI: 10.1097/dcr.0b013e3182a26bfd
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Following Nonoperative Management of Uncomplicated Diverticulitis May Not Be Warranted

Abstract: The incidence of clinically significant neoplasia on endoscopic follow-up after the nonoperative management of acute diverticulitis is 9.2%. Those with complicated diverticulitis are at higher risk, whereas the incidence of clinically significant neoplasia in those with uncomplicated diverticulitis is equal to the incidence in average-risk individuals. Routine diagnostic colonoscopy following the nonoperative management of acute uncomplicated diverticulitis may not be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 16 publications
4
59
1
6
Order By: Relevance
“…From the patients scoped after the acute episode, 4 patients (2.5%) had colorectal cancer (CRC) and any of them had a previous colonoscopy. Curiously, all patients in whom CRC was diagnosed had uncomplicated disease, which is the opposite of what was found in other studies in which the risk of advanced neoplasia was higher only in those with complicated disease [4,6,7]. In our study, no immediate or late complications related to the colonoscopy were reported.…”
contrasting
confidence: 53%
“…From the patients scoped after the acute episode, 4 patients (2.5%) had colorectal cancer (CRC) and any of them had a previous colonoscopy. Curiously, all patients in whom CRC was diagnosed had uncomplicated disease, which is the opposite of what was found in other studies in which the risk of advanced neoplasia was higher only in those with complicated disease [4,6,7]. In our study, no immediate or late complications related to the colonoscopy were reported.…”
contrasting
confidence: 53%
“…Similarly, Brar et al [41] also found that patients with complicated diverticulitis had a significantly higher incidence of AA (18.9 vs. 5%, p = 0.001) and invasive malignancy (5.4 vs. 0%, p = 0.007) compared to patients who presented with uncomplicated diverticulitis.…”
Section: Discussionmentioning
confidence: 93%
“…13,22 It is also not clear whether all the CT scans in the included studies were 64-slice high-resolution scans, as used in our study, which may affect the ability to distinguish malignancy from inflammatory changes. Brar and colleagues 23 reported an overall prevalence of malignancy in CT-scan diagnosed diverticulitis of 1.6%, but complicated diverticulitis with pericolic or pelvic abscess was associated with a higher rate of invasive malignancy: 5.4%. Although our study did not distinguish between complicated and uncomplicated diverticulitis by examining specific radiological features, our results are in line with those of the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%